Social Media Marketing To Improve Awareness Of The Buper Segorogunung Ecotourism Location Owned By Perum Perhutani KPH Surakarta - Diyana Pratiwi Faizah; Erlita Ridanasti (Cita konsultindo, 2024)
Buper Segorogunung Ecotourism is located in the protected forest area of Mount Lawu Utara, Karanganyar, Central Java. This ecotourism offers various outdoor activities, such as camping, jeep tours, and outbound. Despite having great natural potential, this ecotourism is still classified as a pioneering destination with a relatively low level of visits. One of the main causes is the less than optimal use of social media marketing. This study adopted a qualitative approach to obtain data directly from sources related to the use of social media marketing to increase awareness of the Segorogunung Camping Ground ecotourism location owned by Perum Perhutani KPH Surakarta. Based on observations and interviews, it is known that the Segorogunung Camping Ground manager has implemented a promotional strategy by utilizing social media that is active on the Tiktok and Instagram platforms. However, the Segorogunung Camping Ground manager has not been able to maximize this promotional strategy in building awareness of the ecotourism location. In addition to using social media, the manager collaborates with travel agents and communities to expand its target market.